(untitled) - Legge, John M. (New York, 1997)
Entrepreneurship: Context, Vision & Planning enables final year undergraduate and postgraduate students to successfully blend their existing knowledge and skills to create a new enterprise to pursue an opportunity. A comprehensive outline of the historical development of the topic and its underpinnings in history, economics, law and politics sets the context for entrepreneurship before readers encounter practical models and recommendations which enable them to develop successful business plans to command the attention of potential investors. Blending theory and practice throughout, this text uniquely: Emphasises ethical entrepreneurship and argues that successful businesses can generate broad social benefits beyond the entrepreneur and their stakeholders Incorporates a technological awareness reflected in numerous computer and hi tech industry examples and the discussion of rapid change in the diffusion of technology Links entrepreneurship theory with economi cs Provides a detailed methodology for analysing opportunities and identifying likely success and failure rates Considers the future of entrepreneurship and its application under particular social and economic conditions Online lecturer support includes: Comprehensive teaching guide Powerpoint slide presentations for a 12 lecture course Testbank including over 100 short answer questions (with answers)
Keywords: Entrepreneurship; Planning